An elementary model for fast detonations in tubular charges. Issue 4 (4th July 2019) - Brailovsky, Irina; Kagan, Leonid; Gordon, Peter; Sivashinsky, Gregory
Abstract : The paper is concerned with the experimentally known phenomenon that the detonation velocity of a tubular charge may markedly exceed that of a homogeneous charge of the same explosive. It is shown that the effect may be successfully reproduced using a simple quasi-one-dimensional two-layer model assuming the gas–solid system to be isothermal and the volumetric fraction of the solid phase to be small. In view of a considerable drop of the burned gas pressure/density, compared to the Chapman–Jouguet case, fast detonation may be perceived as a variety of weak (undercompressed) detonation.